The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1371/journal.pone.0279171
|View full text |Cite
|
Sign up to set email alerts
|

Cardio-selective versus non-selective β-blockers for cardiovascular events and mortality in long-term dialysis patients: A systematic review and meta-analysis

Abstract: Background Trials in patients receiving dialysis have demonstrated that β-blockers reduce all-cause mortality and cardiovascular events. However, differences still exist within-class comparative effectiveness studies of the therapeutic benefits of β-blockers in dialysis patients. Objective The purpose of this systematic review is to examine whether cardiovascular events and all-cause mortality differed between dialysis patients receiving cardio-selective and non-selective agents. Methods A comprehensive se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…Some studies showed better clinical outcomes with dialyzable and/or cardioselective β-blockers than with non-dialyzable and/or non-cardioselective ones, despite overall inconsistent results between the types of β-blockers and the clinical outcomes [7][8][9][10][11][12][13][14][15][16][17][18]. However, our study did not show superiority in patient survival based on the type of β-blockers.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Some studies showed better clinical outcomes with dialyzable and/or cardioselective β-blockers than with non-dialyzable and/or non-cardioselective ones, despite overall inconsistent results between the types of β-blockers and the clinical outcomes [7][8][9][10][11][12][13][14][15][16][17][18]. However, our study did not show superiority in patient survival based on the type of β-blockers.…”
Section: Discussioncontrasting
confidence: 81%
“…However, they have different characteristics based on dialyzability and/or cardioselectivity, which may result in different effects on the survival of patients with HD. Previous studies have evaluated the association between types of β-blockers and outcomes in patients with HD [7][8][9][10][11][12][13][14][15][16][17][18]. However, results regarding this association were inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…A propensity-matched retrospective cohort study comparing dialysis clearance and morbidity and mortality in dialysis patients on different medications showed that in HD patients, the use of DBBs is associated with an increased risk of death in the subsequent 6 months compared with NDBBs [ 148 ]. It has been suggested [ 149 ] that the use of cardio-selective BB may be associated with fewer CV events and lower all-cause mortality compared with dialysis patients on non-selective BB. A propensity-matched retrospective cohort study [ 150 ] of 3400 HD patients with HF showed lower all-cause mortality in patients treated with BB and even lower mortality in patients treated concomitantly with BB and ACEIs or ARBs.…”
Section: Drug Treatment For Dialysis Patientsmentioning
confidence: 99%
“…A reduction of heart rate might result in increased diastolic filling and improved stroke volume, which is energetically convenient. The use of β-blockers has been shown to improve outcome in ESKD [ 105 , 106 ]. Improvement of diastolic function can be achieved by managing structural, haemodynamic and biological conditions impairing mechanisms of active relaxation and passive filling.…”
Section: Introductionmentioning
confidence: 99%